Implementation of Piercing The Corporate Veil By Shareholders in Limited Liability Companies - Aditya Indra Renaldi; Ridwan Khairandy; Bagya Agung Prabowo (Institute Of computer Science (IOCS), 2022)
This study aims to obtain data and information or information for: Knowing the Implementation of Piercing The Corporate Veil by Shareholders in Limited Liability Company law, Knowing the implementation of Piercing The Corporate Veil by holders share. The approach used in writing this thesis is a normative juridical approach. This means reviewing statutory provisions while still addressing existing problems as well as researching their implementation in practice. only as a tool used by shareholders to fulfill their personal goals, usually these illegal acts are carried out by majority shareholders who do not have good intentions. If a shareholder commits an unlawful or fraudulent act on behalf of the company, he must be responsible for his personal wealth, and this is detrimental to shareholders and stakeholders. Recognition of this principle is something that is generally accepted in any legal system, in the Indonesian legal system it is expressly recognized by UUPT Number 1 of 1995, through Article 3 paragraph (1). 2. Piercing the Corporate Veil by shareholders can be enforced as stated in Article 3 paragraph (2) which states that if there is a mixing of the shareholder's personal assets with the company's assets, then the limited liability will be abolished. The holder of 101 shares is not only responsible for the capital deposited in the company, but must bear the risk to personal assets, if the company suffers a loss, then the responsibility becomes unlimited or no longer a legal act of PT.